Ullmann's Encyclopedia of Industrial Chemistry 2014
DOI: 10.1002/14356007.a11_393.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Fluoropolymers, Organic

Abstract: The article contains sections titled: 1. Introduction 1.1. History 1.2. Monomers 1.3. Polymers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Despite the model shortcomings, it should nonetheless be noted that the presence of fluoropolymers make the recycling process technically and economically challenging because of the characteristic C‐F bond strength . It is also well documented that the thermal decomposition of fluoropolymers is a potential source of persistent compounds such as fluorocarbons, fluoroacids, dioxins, and furans . Even from industrial and specialised high‐temperature thermal degradation systems, it was found that significant amounts of trifluoroacetate can be released into the environment .…”
Section: Life Cycle Impact Assessment—results and Interpretationmentioning
confidence: 99%
“…Despite the model shortcomings, it should nonetheless be noted that the presence of fluoropolymers make the recycling process technically and economically challenging because of the characteristic C‐F bond strength . It is also well documented that the thermal decomposition of fluoropolymers is a potential source of persistent compounds such as fluorocarbons, fluoroacids, dioxins, and furans . Even from industrial and specialised high‐temperature thermal degradation systems, it was found that significant amounts of trifluoroacetate can be released into the environment .…”
Section: Life Cycle Impact Assessment—results and Interpretationmentioning
confidence: 99%
“…Generally, annealing is particularly useful for enhancing the degree of crystallinity, reducing the porosity and eliminating the residual solvent of the P(VDF-TrFE) films [149]. From an economic point of view, P(VDF-TrFE) is more expensive than PVDF, owing to the production risk of explosion of TrFE monomer during co-polymerization [150]. Nevertheless, P(VDF-TrFE) has found wide applications for energy harvesters [151,152], and bone tissue engineering [8].…”
Section: Scaffold Fabricationmentioning
confidence: 99%
“…A previous study of MLD has shown significant differences in the growth characteristics and film properties when monomer lengths are altered . Properties of fluorocarbon-hydrocarbon copolymers are especially sensitive to the length of the individual monomer units . To demonstrate the ability to alter monomer unit lengths for the pMLD synthesis, a 1,7-octadiene (OD) monomer was used for pMLD together with the DIOFB monomer.…”
Section: Resultsmentioning
confidence: 99%